Endogenous circulating testosterone and sex hormone‐binding globulin levels and measures of myocardial structure and function: the Framingham Heart Study. (13th February 2019) - Pencina, K. M.; Travison, T. G.; Bhasin, S.; Li, Z.; Nigam, N.; Manning, W. J.; Vasan, R. S.; Hoffmann, U.; O'Donnell, C. J.; Basaria, S.
Abstract: Background: The relation between endogenous testosterone concentrations and myocardial mass and function remains incompletely understood. Objectives: To determine the cross‐sectional association between endogenous hormone levels with cardiac magnetic resonance measures of myocardial mass, structure, and function in community‐dwelling men across a wide age range. Methods: A total of 720 men from the Framingham Heart Study Offspring Cohort (age range 37–82, mean = 59.6 years) who underwent cardiac magnetic resonance imaging and had hormone levels measured. Total testosterone (measured using liquid chromatography‐tandem mass spectrometry), sex hormone‐binding globulin (measured using an immunofluorometric assay), and calculated free testosterone levels were assessed in male participants of the Framingham Heart Study Offspring Cohort at examination 7. Cardiac magnetic resonance imaging was performed between examinations 7 and 8 (2002–2006). Results: Age‐adjusted linear regression models showed statistically significant association between total testosterone levels and left ventricular mass ( p  = 0.009), left ventricular mass index ( p  = 0.006), cardiac output ( p  = 0.001), and main pulmonary artery diameter ( p  = 0.008); the association between total testosterone and these cardiac magnetic resonance measures was weak and was not significant after adjustment for established risk factors—age, body mass index, diabetes, and hypertension. Furthermore, calculated free testosterone level was not significantly associated with any measure of myocardial mass or function. Sex hormone‐binding globulin level was significantly associated with left ventricular mass ( p  = 0.002), left ventricular mass index ( p  = 0.004), cardiac output ( p  = 0.003), left ventricular ejection fraction ( p  = 0.039), and main pulmonary artery diameter ( p  = 0.042) in age‐adjusted models; these associations were also rendered non‐significant after adjusting for cardiovascular risk factors. Conclusions: Neither testosterone nor sex hormone‐binding globulin levels in men are associated significantly with myocardial mass and function independent of established cardiovascular risk factors.